Synthesis and characterization of cyanocobalamin conjugates with Pt(II) complexes towards potential therapeutic applications - Porębska, Dominika; Orzeł, Łukasz; Rutkowska-Żbik, Dorota; Stochel, Grażyna; van Eldik, Rudi (Polyhedron, 2023)
The increased affinity of cyanocobalamin (CblCN) for cancer cells provided the basis for its use as a carrier of inorganic cytostatics potentially reducing the side effects of chemotherapy. Our studies were focused on the effect of ligands on the stability of platinum(II) conjugates with CblCN. The synthesis of three selected conjugates containing coordinated chloride ions, water molecules, diethylenetriamine or terpyridine were monitored spectrophotometrically and the formation of desired binuclear complexes were confirmed by MS-ESI, 195Pt NMR and IR spectroscopy. In addition, molecular modelling was applied to determine the geometry and binding energies of the conjugates. According to our results, the expansion of the coordination sphere of the therapeutic metal negatively affects the stability of conjugates with CblCN, which can be considered as expected in the context of their anticipated intercalation ability.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Binuclear complexes; Cyanocobalamin; Drug delivery; Platinum(II) complexes